Students' Attitude and Teachers Towards Blended Learning Model in Class XI Biology Subjects at State High School in Makassar - Nur Rabiy’atul Awaliyah; Syamsiah Syamsiah; Firdaus Daud (Biology Teaching and Learning, 2023)
Abstract. The attitude of students and teachers towards the Blended Learning Model in Biology class XI at SMA Negeri Makassar is a descriptive quantitative research. The purpose of this study was to determine the attitudes of students and teachers towards the Blended Learning Model in class XI Biology at SMA Negeri Makassar. The research was conducted from April to May 2022 at SMA Negeri 21 Makassar, SMA Negeri 18 Makassar, SMA Negeri 6 Makassar, SMA Negeri 17 Makassar, and SMA Negeri 10 Makassar. The research instrument used a questionnaire on the attitudes of students and teachers. The data analysis process was carried out using SPSS ver.23. The results of the study showed that students' attitudes towards Blended Learning Model in Biology class XI at SMA Negeri Makassar were in the neutral category with a percentage of 38% and teachers' attitudes towards Blended Learning Model in Biology class XI at SMA Negeri Makassar were at negative category with a percentage of 50%.Keywords: students and teachers attitude, blended learning model